Pandemia y crisis. Desafíos para las ciencias sociales. - Vidal, Paula; Assael, Jenny; Facuse, Marisol; Gomez, Andrés; Miranda, Christian; Urrutia, Miguel; Castillo, César (Social-ediciones, 2022)
Pandemic and social crisis are the two phenomena that provide the context in which this book emerges. The work of the social sciences in this context is more relevant and challenging than ever, because it is clear that in the crisis -from the pandemic in Chile-, economic, social and political-institutional crises converge, which made its analysis and overcoming strategies much more complex, considering the need and urgency of an epochal change. In these convulsive times, from the Faculty of Social Sciences of the University of Chile, we set out to gather investigations from different disciplines and intersections of knowledge to contribute to the understanding of this particular historical moment and its repercussions in Chilean society in order to thereby contribute to improving the lives of the people affected by this crisis from various spheres and dimensions.